Prohibition of Marriage Within Villages in a Review of Customary and Islamic Law - Ahmad Faisal (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
In Islam, the term mahram means a person who is forbidden to marry. Although Islam has determined it, in jorong Bandar Mas nagari Cubadak Pasaman district, there is a tradition of prohibiting marriage relations for reasons outside the provisions of shara', namely, a man is prohibited from marrying a woman who is still in the same village with the man. Therefore, the author is interested in conducting research with the type of qualitative research that aims to understand the prohibition of marriage in one village. The results showed that one village marriage in the version of the Bandar Mas jorong community is a pantang marriage. Kawin pantang in Minangkabau custom can be understood as a marriage that is prohibited by custom or a marriage that cannot be carried out or held based on the values agreed upon in custom. In Islamic law, women who cannot be married are called mahrams. Linguistically, the term mahram comes from the word haram, which means forbidden or not allowed. The prohibition of marriage in the same village is not known in Islam. Regarding the prohibition of marriage in the same village, a common ground can be found between the two. Customary law can be considered to strengthen Islamic law. Marriage with someone other than a relative will strengthen the offspring, as reported by the Companions and the opinion of Imam Ghazali.